ВЗАЄМОЗВ’ЯЗОК ІНФОРМАТИКИ ТА МАТЕМАТИКИ В ШКОЛІ НА РАННЬОМУ ЕТАПІ ВИВЧЕННЯ - Kondor , Daryna; Yurchenko , Nataliia (Науковий вісник Ужгородського університету. Серія: «Педагогіка. Соціальна робота», 2025)
Актуальність обраної теми дослідження полягає у висвітленні питання, пов’язаного з формуванням алгоритмічного мислення в учнів молодшого шкільного віку на уроках інформатики. Метою статті є виявити роль інформатики та математики у формуванні алгоритмічного стилю мислення. Для досягнення мети використовувалися наступні методи: аналіз, порівняння, спостереження, синтез. Також було використано обробку даних статистичними методами. У статті зазначено, що основою для алгоритмічного мислення є формування математичної компетентності молодших школярів. На уроках інформатики школярі практичними методами застосовують набуті знання з математики. Тому важливим є відповідний рівень знань учнів з математики. В статті наведено таблицю рівнів успішності з математики та з інформатики учнів третіх та четвертих класів однієї з початкових шкіл міста Ужгорода. Порівняно рівень успішності вивчення математики з рівнем успішності вивчення інформатики третьокласниками та аналогічно четвертокласниками. При порівнянні двох емпіричних розподілів ми скористалися двовибірковим критерієм узгодженості Колмогорова-Смирнова. Нами показано, що обрані генеральні сукупності є стохастично еквівалентними. The relevance of the chosen research topic is to highlight the issue related to the formation of algorithmic thinking in primary school students in computer science lessons. The aim of the article is to identify the role of computer science and mathematics in the formation of algorithmic thinking style. To achieve this goal, the following methods were used: analysis, comparison, observation, synthesis. Statistical data processing was also used. The article states that the basis for algorithmic thinking is the formation of mathematical competence of junior high school students. In computer science lessons, students apply the acquired knowledge of mathematics by practical methods. Therefore, the appropriate level of students’ knowledge of mathematics is important. The article presents a table of success levels in mathematics and computer science for third and fourth graders of one of the primary schools in Uzhhorod. The level of success in studying mathematics was compared with the level of success in studying computer science by third-graders and similarly by fourth-graders. When comparing the two empirical distributions, we used the two-sample Kolmogorov-Smirnov agreement criterion. We have shown that the selected general populations are stochastically equivalent. Comparing the results of educational achievements in computer science and mathematics of students of 3rd and 4th grades, we came to the conclusion that the formation of mathematical competence helps in solving problems in computer science lessons that require logical thinking and algorithmic skills. We believe that more attention should be paid to the study of the basics of programming in school, the development of logical and algorithmic thinking in mathematics and computer science, as well as in elective classes.